WITHDRAWN: Multimodal data analysis and integration for multi-slot spectrum auction based on Deep Feedforward Network. (December 2017) - Zhao, Feng; Zhang, Yuyi; Chen, Hongbin
Abstract : This article has been withdrawn at the request of the editor and publisher. The publisher regrets that an error occurred which led to the premature publication of this paper. This error bears no reflection on the article or its authors. The publisher apologizes to the authors and the readers for this unfortunate error. The full Elsevier Policy on Article Withdrawal can be found athttp://www.elsevier.com/locate/withdrawalpolicy .